2016
DOI: 10.4103/0973-1482.150362
|View full text |Cite
|
Sign up to set email alerts
|

Increased osteopontin protein expression may be correlated with poor prognosis in non-small-cell lung cancer: A meta analysis

Abstract: The present meta-analysis is consistent with the hypothesis that increased expression of OPN protein may be significantly associated with poor prognosis in patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…These data are also consistent with previous observations by Collins et al (2012) who demonstrated that higher SPP1 expression is beneficial since it was associated with an improved outcome in patients with pancreatic cancer [42]. By contrast, several other investigations highlighted that high SPP1 levels were correlated with poor outcomes in many solid malignancies such as prostate cancer, lung cancer, gastric cancer and breast cancer [43][44][45][46]. For instance, Wong et al (2017) showed that the overexpression of SPP1 in bladder cancer patients with high T-stage and tumor grades was significantly associated with decreased patient survival time [47].…”
Section: Discussionsupporting
confidence: 91%
“…These data are also consistent with previous observations by Collins et al (2012) who demonstrated that higher SPP1 expression is beneficial since it was associated with an improved outcome in patients with pancreatic cancer [42]. By contrast, several other investigations highlighted that high SPP1 levels were correlated with poor outcomes in many solid malignancies such as prostate cancer, lung cancer, gastric cancer and breast cancer [43][44][45][46]. For instance, Wong et al (2017) showed that the overexpression of SPP1 in bladder cancer patients with high T-stage and tumor grades was significantly associated with decreased patient survival time [47].…”
Section: Discussionsupporting
confidence: 91%
“…In a selection of 10 clinical cohort studies represented by a total of 1133 NSCLC patients, Shi et al showed a shorter overall survival in OPN-positive patients compared to that in OPN-negative patients with no significant differences between the Asian and the Caucasian groups, thus suggesting a role for OPN as a prognostic factor for NSCLC [102]. Moreover, the analysis by Hu et al of a cohort of six studies, with a total of 906 participants, of which 360 were MPM patients and 546 healthy individuals, showed that the diagnostic accuracy of OPN for MPM was comparable to that of the soluble mesothelin-related peptides (SMRP), the most promising serum biomarker for MPM [103].…”
Section: Systemic Opn Levels In Cancermentioning
confidence: 99%
“…Although OPN is not tumor-specific, its potential as a tumor biomarker has been demonstrated in several malignancies, including breast cancer [ 3 , 4 ]. Elevated OPN expression has been associated with poor survival of cancer patients with different tumor histotypes [ 5 8 ]. Moreover, high OPN plasma concentrations were found in patients with metastatic breast cancer compared to healthy volunteers [ 9 ], while a number of studies have demonstrated that OPN may be associated with breast cancer progression and metastasis [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%